Abnormal evening vertical plasma drift and effects on ESF and EIA over Brazil-South Atlantic sector during the 30 October 2003 superstorm - Abdu, M. A. (2008)
Equatorial F region vertical plasma drifts, spread F and anomaly responses, in the south American longitude sector during the superstorm of 30 October 2003, are analyzed using data from an array of instruments consisting of Digisondes, a VHF radar, GPS TEC and scintillation receivers in Brazil, and a Digisonde and a magnetometer in Jicamarca, Peru. Prompt penetrating eastward electric field of abnormally large intensity drove the F layer plasma up at a velocity 1200 ms−1 during post dusk hours in the eastern sector over Brazil. The equatorial anomaly was intensified and expanded poleward while the development of spread F/plasma bubble irregularities and GPS signal scintillations were weaker than their quiet time intensity. Significantly weaker F region response over Jicamarca presented a striking difference in the intensity of prompt penetration electric field between Peru and eastern longitudes of Brazil. The enhanced post dusk sector vertical drift over Brazil is attributed to electro-dynamics effects arising energetic particle precipitation in the South Atlantic Magnetic Anomaly (SAMA). These extraordinary results and their longitudinal differences are presented and discussed in this paper.